Increased expression of calponin 2 is a positive prognostic factor in pancreatic ductal adenocarcinoma - Qiu, Zhaoyan (Oncotarget, 2017)
Calponin 2 plays an important role in regulating actin cytoskeleton, which is critical for cell division and migration. Previous studies have demonstrated that calponin 2 inhibits prostate cancer cell proliferation and metastasis. However, the role of calponin 2 in pancreatic tumor growth, metastasis and patient survival remains unclear. Here, we demonstrate that the level of calponin 2 is a positive prognostic factor for patients with pancreatic ductal adenocarcinoma (PDAC). Patients with high calponin 2 expression in the tumor presented less lymph node metastasis and longer survival. Knockdown of calponin 2 facilitated pancreatic cancer cell proliferation and metastasis. Further experiments suggested that PI3K/AKT, NF-κB, Vimentin, Fibronectin, Snail and Slug were upregulated and E-cadherin was downregulated after calponin 2 was knocked down, implicating altered functions in PDAC proliferation and metastasis. In addition, we verified that calponin 2 functioned through inhibiting PI3K/AKT and NF-κB pathways. Our study suggests that the upregulation of calponin 2 in PDAC correlates to lower malignancy and presents a novel target for the development of new treatment.